Diversity of Lasiodiplodia Species Associated with Canker and Dieback in Fruit Trees in the Henan and Shandong Provinces of China - Wang, Yanfen (Plant disease, 2024)
Lasiodiplodia is a widely distributed genus that is associated with a variety of diseases in many plant species, especially fruit trees. In this study, a disease survey of fruit trees growing in 12 orchards located in the Henan and Shandong provinces of China was conducted between 2020 and 2022. The symptoms observed included stem canker, branch dieback, and gummosis. Phylogenetic analyses of internal transcribed spacer, tub2, tef1, and rpb2 sequence data combined with morphological characteristics revealed that the 19 isolates collected during the survey belonged to five documented Lasiodiplodia species, namely, Lasiodiplodia citricola, L. chiangraiensis, L. huangyanensis, L. pseudotheobromae, and L. theobromae, and two previously undescribed species, L. xinyangensis and L. ziziphi. In addition, the survey identified three novel host-pathogen interactions: L. chiangraiensis on loquat, L. citricola on apple, and L. huangyanensis on grapevine. Furthermore, the detailed phylogenic analysis indicated that four previously described Lasiodiplodia species were genetically very closely related that they would be better classified as synonyms rather than distinct species, so L. paraphysoides and L. nanpingensis should be considered synonyms of L. citricola, L. fujianensis should be a synonym of L. iraniensis, and L. henanica should be a synonym of L. huangyanensis. Pathogenicity tests confirmed that representative isolates of the two novel species and three new host-pathogen interactions identified in the current study were pathogenic to their original hosts, thereby fulfilling Koch's postulates. Similarly, all of the isolates were found to be pathogenic on four alternative hosts, although a high degree of variation in virulence was observed